2004
DOI: 10.1590/s0100-879x2004000600003
|View full text |Cite
|
Sign up to set email alerts
|

Different stress modalities result in distinct steroid hormone responses by male rats

Abstract: Since both paradoxical sleep deprivation (PSD) and stress alter male reproductive function, the purpose of the present study was to examine the influence of PSD and other stressors (restraint, electrical footshock, cold and forced swimming, N = 10 per group) on steroid hormones in adult Wistar male rats. Rats were submitted to chronic stress for four days. The stressors (footshock, cold and forced swimming) were applied twice a day, for periods of 1 h at 9:00 and 16:00 h. Restrained animals were maintained in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(82 citation statements)
references
References 34 publications
(44 reference statements)
5
70
0
7
Order By: Relevance
“…Our group and others (Marinelli et al, 2007) have previously shown that yohimbine produces significant increases in circulating CORT levels and, in the present study, we show that yohimbine administration in ethanol-extinguished rats causes a nonsignificant increase in progesterone levels (Supplementary Figure 1). However, the levels in the male rats described here remain very low and are quite close to basal levels reported in the literature (Andersen et al, 2004(Andersen et al, , 2005Auger et al, 2006). Additional experiments with more selective ligands for GR and PR are necessary to fully determine the mechanism of action for mifepristone's effect on yohimbine-induced reinstatement of ethanol-seeking.…”
Section: Discussionsupporting
confidence: 78%
“…Our group and others (Marinelli et al, 2007) have previously shown that yohimbine produces significant increases in circulating CORT levels and, in the present study, we show that yohimbine administration in ethanol-extinguished rats causes a nonsignificant increase in progesterone levels (Supplementary Figure 1). However, the levels in the male rats described here remain very low and are quite close to basal levels reported in the literature (Andersen et al, 2004(Andersen et al, , 2005Auger et al, 2006). Additional experiments with more selective ligands for GR and PR are necessary to fully determine the mechanism of action for mifepristone's effect on yohimbine-induced reinstatement of ethanol-seeking.…”
Section: Discussionsupporting
confidence: 78%
“…The glucocorticoids are able to stimulate the glucogenesis by the liver, directly acting in the phosphoenolpyruvate carboxykinase enzyme (PEPCK) or indirectly through the augmented sensibility of the hormones responsible for the hepatic glycolysis, adrenaline and glucagon (38) . However, excessive HHA axis activation and consequent increases in the plasma concentrations of corticosterone, may lead to homeostasis rupture and undesirable effects to the body (3,34) .…”
Section: Adrenal Cholesterol Experimental Groupsmentioning
confidence: 99%
“…Physical exercise is known to be a stressor stimulus both in humans and animals which leads to countless physiological alterations aiming to provide the augmentation of the energetic demand as well as the reach for a new situation of homeostasis (1)(2)(3) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations